(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article discusses the linguocultural, ethnocultural identity of the Wormwood lexeme, which has a special sacral significance in the linguistic consciousness and worldview of the Kazakh people, which has been used by our ancestors since ancient times. It is impossible to separate the linguocultural concept of any language from the worldview, ethnoculture, historical relics, spiritual essence, psychology, national cultural code, traditions and rituals of the collective consciousness of the user of this language. In this regard, the material-logical picture of objects and phenomena in the environment is marked by language. In the history of the existence of each ethnic group, there are many things that are directly connected with a culture that has its own value. These are: names of plants and species, names of celestial bodies and animals, names of animals and oritonyms, numerical systems and units of measurement, kinship names and gender names. Our ancestors, as Native children of nature, closely observed the plant world in the Kazakh steppes and widely used their noble qualities in their lifetime practice. Based on the accumulated extensive experience, the botanists and academics of the Great Steppe knew deeply that plants are our life – support, our life – food, clothing, food, use, bed, paper. Therefore, our ancestors, who firmly consumed the nomadic way of life, were most aware of the food, healing and nutritional aspects of plants. Therefore, this article considers the lingo-cultural model and algorithmic matrix of the phytonym “Zhusan”, which is a steppe Musk, as a complex system. Semantic analysis of the etymological meaning of the lexeme “Zhusan” and the associative layer and symbolic meaning of Zhusan – Atameken, Zhusan – sagynysh, Zhusan – boybala, Zhusan – childhood, Zhusan – bank, Zhusan – steppe Musk, Zhusan – direction-orientation is carried out. It turns out that the phytonym “Zhusan” in our language is a lexeme that forms a semantic paradigm that has associative and symbolic features. Key words: associative layer, Zhusan, linguoculturology, symbolic meaning, lexeme.